A disulfide-constrained miniprotein with striking tumor-binding specificity developed by ribosome display - Zoller, Frederic; Hebling, Ulrike; Altmann, Annette; Lindner, Thomas; Mier, Walter; Haberkorn, Uwe (Angewandte Chemie. International edition, 2013)
Fold me to hold me: A specific binding agent against the delta-like ligand 4 protein, which is expressed in angiogenesis, was identified by ribosome display. Specific tumor binding of this molecular imaging agent depends on the appropriate disulfide connectivity of its scaffold.
Gesehen am 02.08.2021